An industrial quality control study at Cancorp Inc. Rowell Group of Companies - Enderez, Anatolio (College of Engineering, 2004)
This is a Quality Control Study performed at the tin can manufacturing corporation Cancorp, Incorporated. The study focused on the company's most manufactured product, tin cans with diameter of 127 mm. The study documented the entire can manufacturing process of the company. The company's quality control data were utilized in calculating performance measures based on statistical quality control formulas. The Failure Mode and Effects Analysis (FMEA) methodology was employed in identifying potential process problems. Failure modes were identified and each were rated with respect to their severity, occurence and detection. A Risk Priority Number was calculated for each failure mode. Using the RPN, the most critical failure modes were identified and were focused on in the formulation of recommendations. Statistical Process Control Charts were formulated for the major attributes of the product. For each control chart, the distributions of the corresponding attributes were superimposed over the specification limits to project whether the data was well centered or not. Process recommendations that would improve process averages were formulated. The acceptance sampling plan employed by the Company was evaluated in terms of statistical quality control performnace mesaures. It is recommended to cease the use of the inverter test used in weld inspection and use the samples as an additional sample for the moreaccurate ball-tear test. The main recommendations of the study were basically the utilization of the company's quality control data thru set-up of control charts that would definitely improve quality. Process changes that would aid in the improvement of the statistical distributions of attributes were also recommended. Specifically, the reduction of the flange width and the tightening of the seam were highly recommended because such would improve all attributes and thus center the data inside the specification limits. Overall, te study was mostly documentation and presentation of formulated Statistical Quality Control Charts. The recommendations were few but concise and very relevant and beneficial. The importance of employing statistical quality control tools in monitoring the company's process was emphasized throughout the study.